PEMBELAJARAN KARAKTER DISIPLIN MELALUI PENDIDIKAN SENI DI SD NEGERI 26 KAYU PASAK KECAMATAN PALEMBAYAN KABUPATEN AGAM - Novia Rita; Farida Mayar; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
In the subject of music, there is one of the character values used to achieve the competence of students, namely discipline. The objective to be achieved in this research is to find out the character learning discipline through art education in 20 Kayu Pasak State Elementary School. This type of research is a qualitative research, carried out in Sumberejo State Elementary School 20 Kayu Pasak Subdistrict Palembayan Elementary Agam District in 2022/2023 school year. Sources of data in this study were obtained through interviews, filling out questionnaires, and documentation from informants. The results of this study are based on observations and interviews of principals and teachers and filling out questionnaires (questionnaire) class III SD Negeri 26 Kayu Pasak already carrying out character discipline learning through art education (SBdP). It can be seen that students obey all school rules.